Literature Review: Cyberbullying in Addolescence - Marpatmawati, Idhfi; Yuningsih, Aneng; Rismawan, Wawan; Milda Hidayat, Nandita (Yayasan Inspirasi El Burhani, 2024)
Introduction: Cyberbullying is a growing phenomenon with the increasing use of digital technology and social media among adolescents. This phenomenon can affect adolescents' mental and emotional well-being, even having long-term impacts on their psychological health. This study aims to reveal the prevalence, risk factors, and psychological impact of cyberbullying among adolescents. Objective: This study aims to explore the prevalence, risk factors, and psychological impact of cyberbullying among adolescents, with a focus on the relationship between cyberbullying and mental health outcomes such as depression, anxiety, and suicidal ideation. Method: This study used a literature search design with articles searched through three search engines: Ebsco, Proquest, and Google Scholar. The articles used were research conducted within the last five years (2020-2025), using the keywords